Clinton in exile : a president out of the White House - Felsenthal, Carol (New York : William Morrow, 2008)
An evaluation of the post-presidential life of Bill Clinton draws on interviews with friends, associates, and adversaries to address questions about how he has adjusted to a life of reduced power, the nature of his relationship with Hillary, and the state of his health.
Oh, for just one more term -- The best house -- Getting serious, studying the legacy of Jimmy Carter -- Not quite ready for prime time -- Clinton opens his Library in a downpour -- Bill Clinton fixes Africa -- The path to 9/11 -- A Luddite meets the Bloggers -- Philanderer in chief -- Hillary's (and Bill's) run for the White House -- First Gent: a Dolley Madison for the twenty-first century? -- Getting the full Clinton-- pro bono -- It's Monica, stupid!
Includes bibliographical references and index.
Keywords: Clinton, Bill, -- 1946-; Clinton, Bill, -- 1946-; Presidents -- United States -- Biography; Presidents -- United States -- Biography; United States -- Politics and government